Peningkatan Pengetahuan Ibu Nifas dan Menyusui Tentang MP-ASI (Makanan Pendamping ASI) di RS Citra Sari Husada - Puput Putri Apriliyani; Masruroh (Universitas Ngudi Waluyo, 2025)
Babies are newborn creatures and have a body condition that is still vulnerable, therefore babies need the right nutritional intake to support their growth and development. Breast milk (ASI) is the best natural nutrition for babies with the most appropriate nutritional content for optimal growth. The availability of smooth breast milk in breastfeeding mothers will help the success of exclusive breastfeeding for 6 months, thus helping babies grow and develop well according to recommendations from the World Health Organization (WHO). After 6 months, complementary feeding is started according to recommendations from WHO and the Ministry of Health. The problem of breastfeeding in Indonesia includes Early provision of complementary feeding, Exclusive breastfeeding Data from the Indonesian Central Statistics Agency (BPS) shows that in 2022, there were 72.04% of babies who did not receive exclusive breastfeeding, which could be related to early provision of complementary feeding, Research shows that factors such as maternal education, knowledge of complementary feeding, family support, and socio-cultural conditions can influence the practice of providing complementary feeding. The government's efforts to increase knowledge about providing complementary feeding are by providing counseling to postpartum and breastfeeding mothers in preparation for providing complementary feeding. The method in this study is descriptive in the form of a case study, namely examining a problem through a case consisting of a group of postpartum and breastfeeding mothers who have knowledge problems in providing complementary feeding. The implementation was carried out in January 2025 by explaining directly to 12 respondents of postpartum and breastfeeding mothers who were in accordance with the targets at Citra Sari Husada Hospital. Abstrak Bayi adalah makhluk yang baru lahir dan memiliki kondisi tubuh yang masih rentan, oleh sebab itu bayi memerlukan asupan nutrisi yang tepat untuk mendukung tumbuh kembangnya. Air susu Ibu (ASI) merupakan nutrisi alamiah terbaik bagi bayi dengan kandungan gizi paling sesuai untuk pertumbuhan optimal. Ketersediaan ASI yang lancar pada ibu menyusui akan membantu kesuksesan pemberian ASI eksklusif selama 6 bulan, sehingga membantu bayi tumbuh dan berkembang dengan baik sesuai rekomendasi dari World Health Organization (WHO). Setelah 6 bulan pemberian MP-ASI dimulai sesuai dengan rekomendasi WHO dan Kementerian Kesehatan. Adapun masalah pemberian asi di Indonesia meliputi Pemberian MPASI dini, Pemberian ASI eksklusif Data dari Badan Pusat Statistik Indonesia (BPS) menunjukkan bahwa pada tahun 2022, terdapat 72,04% bayi yang tidak mendapatkan ASI eksklusif, yang bisa jadi berkaitan dengan pemberian MPASI dini, Penelitian menunjukkan bahwa faktor seperti pendidikan ibu, pengetahuan tentang MPASI, dukungan keluarga, dan kondisi sosial budaya dapat mempengaruhi praktik pemberian MPASI. Upaya pemerintah dalam meningkatkan pengetahuan terhadap pemberian MP-ASI yaitu dengan pemberian penyuluhan kepada ibu nifas dan menyusui dalam persiapan pemberian MP-ASI. Metode dalam penelitian ini diskriptif yang berupa studi penelaahan kasus (case study) yaitu meneliti suatu permasalahan melalui suatu kasus yang terdiri dari kelompok ibu nifas dan ibu menyusui yang memiliki masalah pengetahuan dalan pemberian MP-ASI. Pelaksanaan telah dilakukan pada bulan januari 2025 dengan menjelaskan langsung kepada 12 responden ibu nifas dan menyusui yang sesuai dengan sasaran di RS Citra Sari Husada.